ANALISIS KEBIJAKAN PUBLIK DELIBERATIF DALAM PEMBANGUNAN DAERAH DI KECAMATAN SEMARANG UTARA - Maria Aprilia; Kismartini Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Musrenbang as a means of development planning shoulde be a deliberative nature in fact not yet as deliberative as expected. This research aims to analyze the implementation of public policy analysis on regional development in Kecamatan Semarang Utara, the factors are supporting and inhibiting implementation, than to formulate for renewed efforts that we need to create Musrenbang in Semarang utara as a one of regional development that showed deliberative values. The result of the research showed that Musrenbang which implemented at Kecamatan Semarang Utara have not fulfilled a deliberative aspects that required, especially on the influence and deliberation aspect. In fact the determination of participants musrenbang has not been implemented through random selection, discussion do not provide comprehensive problems, an escort proposal post-Musrenbang Kecamatan very hard to do, and participation residents who still be on a level apparent participation. Based on that situations, need to efforts starting from increases the budget funds, the provision of socialization and information on time, and hold many activities like “Rembug Warga” to create a Musrenbang as a regional development process that showed the deliberative values.